A PROPOSAL FOR A DICTIONARY OF SYNONYMS OF ADVERBIAL AND PREPOSITIONAL PHRASES FROM PORTUGUESE TO ITALIAN - Carvalho Bertonha, Fabio Henrique de [UNESP]; Zavaglia, Claudia [UNESP] (Assoc Nac Pos-graduacao Pesquisa Letras & Linguistica, 2019)
This study analyses adverbial and prepositional phrases composed of 'a','de', and `em', which contributed to the design of our Portuguese-Italian special dictionary, from its macrostructure to its microstructure. Based on Lyons (1977), Tamba-Mecz (2006), and Regueiro Rodriguez (2013), we suggest that two or more words can be considered synonyms in a language if they are interchangeable in a given context, without meaning alteration, in another. Once we imply that the equivalence between languages is a sine qua non condition for the elaboration of bilingual dictionaries, we elaborate a prototype entry, which includes contexts of use in order to certify the occurrence of adverbial and prepositional phrases under study. We validate the use of the equivalent phrase(s) by means of web search engines. Thus, we verify the correspondence of synonymic occurrences, or rather, whether the contexts of use in source and target languages are the same. Our results show the presence of synonymic equivalents as adverbial and prepositional phrases, as well as the recurrence of adverbs ending in `-mente' functioning as synonyms, both in Portuguese and Italian (both inter- and intra-linguistically). For this reason, we highlight the importance of synonymy as a language phenomenon, especially for translators, since it can lead them to the most appropriate equivalents in a particular context
Keywords: Adverbial and Prepositional Phrases; Synonymy; Bilingual Lexicography; Dictionary